Predicting peer-assisted study session attendance. (November 2019) - Allen, Peter J; Tonta, Kate E; Haywood, Sophie B; Pereira, Raphael M; Roberts, Lynne D
Peer-assisted study session attendance is associated with multiple indicators of student success. However, attendance levels are generally low. We applied an extended theory of planned behaviour model, incorporating student role identity, to the prediction of peer-assisted study session attendance. Participants were 254 undergraduate students enrolled in 24 peer-assisted study session supported units. Attitudes, subjective norms and perceived behavioural control each had a significant direct effect on attendance intentions, which had a significant direct effect on attendance. All three predictors also had significant indirect effects on attendance, mediated by intentions. After controlling for intentions, only perceived behavioural control had a significant direct effect on attendance. The model accounted for 61% and 42% of the variance in intentions and attendance, respectively. Student role identity did not improve the predictive utility of the model. Theory of planned behaviour–informed strategies for increasing peer-assisted study session attendance are recommended.